2015
DOI: 10.12657/denbio.073.002
|View full text |Cite
|
Sign up to set email alerts
|

Different growth patterns of Picea schrenkiana subsp. tianshanica (Rupr.) Bykov and Juglans regia L. coexisting under the same ecological conditions in the Sary-Chelek Biosphere Reserve in Kyrgyzstan

Abstract: Abstract:The main aim of the study was to compare the radial growth of Persian walnut and Schrenk spruce trees growing under the same ecological conditions in the Sary-Chelek range of the Tien-Shan Mountains, as well as to analyse the response of these species to the selected climate factors in line with the altitude gradient. Four study plots were established at the altitude of 1350, 1400, 1450 and 1500 m a.s.l. Results indicated that (1) walnut and spruce in the Sary-Chelek Biosphere Reserve have different p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 8 publications
2
5
0
1
Order By: Relevance
“…Correlations with temperatures in current July, especially with maximum temperature is also in agreement with Borscheva's results (1983) which showed that, in July LW formation starts and we see that temperature has the primal effect on this process. Negative correlations with temperature in July are also in agreement with results published by Magnuszewski et al (2015). It can be also considered as a manifestation of drought stress, because low precipitation and high temperature can affect the production of sugars (LaMarche, 1974).…”
Section: Discussionsupporting
confidence: 88%
“…Correlations with temperatures in current July, especially with maximum temperature is also in agreement with Borscheva's results (1983) which showed that, in July LW formation starts and we see that temperature has the primal effect on this process. Negative correlations with temperature in July are also in agreement with results published by Magnuszewski et al (2015). It can be also considered as a manifestation of drought stress, because low precipitation and high temperature can affect the production of sugars (LaMarche, 1974).…”
Section: Discussionsupporting
confidence: 88%
“…Even though the elevation was not specifically targeted, it was tested as altitude has a known effect on tree growth (Coomes & Allen 2007). However, the results of the presented research matched those reported in earlier studies (Monserud & Sterba 1996;Adams et al 2014;Magnuszewski et al 2015). In addition, the same effect has been reported by different studies in different climate zones, e.g.…”
Section: Terrain Attributes and Wetness Indexsupporting
confidence: 82%
“…temperate zones (in the presented dissertation), and semi-arid zones (Adams et al 2014), and this lends support to the findings. The effect of altitude was also proven to be significant and small differences in altitudes have been seen to affect some forest trees species (Magnuszewski et al 2015). For the sake of discussion, one could argue that the effects of the elevation may reflect the vertical distance to the groundwater, and not to allude to any low variations of elevation within the study area, therefore this particular observation must be interpreted with caution.…”
Section: Terrain Attributes and Wetness Indexmentioning
confidence: 90%
See 1 more Smart Citation
“…The local climate is humid continental with relatively warm summers and mild but snowy winters. The long-term average annual air temperature in the nearby village Arkit (~10 km south of Sary Chelek, ~1300 m asl) is about 8°C; January and July means are about −5°C and 19°C, respectively (Magnuszewski et al, 2015). The average annual rainfall amounts to about 900–1000 mm (Academy of Science of the Kyrgyz SSR, 1987; Magnuszewski et al, 2015) with monthly averages of 120–150 mm from March to May, ~40 mm in August and September, and 60–80 mm between December and February (Magnuszewski et al, 2015).…”
Section: Study Sitementioning
confidence: 99%